Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Winter bioenergetics in freshwater fishes: Knowledge gaps and model evaluation - Connor Reeve; Zoe A. Zrini; Christian J. Bihun; Lauren E. Rowsey; Megan K. Murphy; Ben Speers-Roesch; Jacob W. Brownscombe; Steven J. Cooke; Graham D. Raby (Fisheries Research, 2026)

Effects of gill and muscle biopsies on the short‐term behaviour, exercise performance and survival of juvenile lake trout ( Salvelinus namaycush ) - Laura Haniford; Connor H. Reid; Gillian Zorn; Graham D. Raby; Steven J. Cooke (Journal of Fish Biology, 2026)
Non‐lethal biopsy is a valuable tool for gaining insight into the physiological status of fish in the wild and for predicting their subsequent behaviour and survival. However, linking the insights from biopsy to post‐release behaviour relies on the assumption that the biopsy itself has no meaningful impact on post‐release behaviour or survival (e.g. in animals tagged with electronic devices). This assumption is likely to be questioned by fishery managers, animal ethics committees, and other researchers. To date, there has been very little work to assess the sublethal (or lethal) effects of biopsies on fish, and no such studies have evaluated fine‐scale behaviours. Here, muscle and gill tissue samples were taken (both individually and as a combined treatment) from hatchery‐reared juvenile lake trout ( Salvelinus namaycush ) in captivity. Twenty‐four hours after sampling, we used two behavioural assays (behaviour within a Z maze and flight initiation distance) and quantified exhaustive exercise performance to determine whether biopsies impacted behaviour or physiology when compared to non‐sampled controls. We found no evidence that biopsies had any influence on exploratory and shelter‐seeking behaviour in the maze, flight initiation distance, or time to exhaustion (as a proxy for swimming performance). Mortality during a 7‐day monitoring period was very low (2% across treatments) and limited to fish that received either a gill biopsy or the combined biopsy treatment. This study provides empirical support for the use of non‐lethal biopsy in juvenile salmonids as a means of collecting physiological data on individuals in behavioural studies and experiments.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Development and in-vitro assessment of novel oxygen-releasing feed additives to reduce enteric ruminant methane emissions - Alison Graham; Camilla Thorn; Michael McDonagh; Caroline O'Donnell; Stephen Nolan; Stuart F. Kirwan; Sandra O'Connor; Corine O. Nzeteu; Alejandra C.V. Montoya; Andrew Bartle; Alison Hall; Cathy Abberton; et al. (Science of The Total Environment, 2025)

Antimicrobial resistant Enterobacterales of clinical importance in mute swans - Aneta Kovarova; Graham Prole; Maeve Louise Farrell; Mark Maguire; Louise Catherine Murphy; Alexandra Chueiri; Louise O'Connor; Georgios Miliotis; Dearbháile Morris; Liam P. Burke (Science of The Total Environment, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Don't bite the hand that feeds you: Meta food webs help in the face of the Eltonian shortfall - Christophe Botella; Pierre Gaüzère; Louise O'Connor; Julien Renaud; Yue Dou; Catherine H. Graham; Peter H. Verburg; Luigi Maiorano; Wilfried Thuiller (Global Change Biology, 2024)

Land‐use intensity influences European tetrapod food webs - Christophe Botella; Pierre Gaüzère; Louise O'Connor; Marc Ohlmann; Julien Renaud; Yue Dou; Catherine H. Graham; Peter H. Verburg; Luigi Maiorano; Wilfried Thuiller (Global Change Biology, 2024)
Land use intensification favours particular trophic groups which can induce architectural changes in food webs. These changes can impact ecosystem functions, services, stability and resilience. However, the imprint of land management intensity on food‐web architecture has rarely been characterized across large spatial extent and various land uses. We investigated the influence of land management intensity on six facets of food‐web architecture, namely apex and basal species proportions, connectance, omnivory, trophic chain lengths and compartmentalization, for 67,051 European terrestrial vertebrate communities. We also assessed the dependency of this influence of intensification on land use and climate. In addition to more commonly considered climatic factors, the architecture of food webs was notably influenced by land use and management intensity. Intensification tended to strongly lower the proportion of apex predators consistently across contexts. In general, intensification also tended to lower proportions of basal species, favoured mesopredators, decreased food webs compartmentalization whereas it increased their connectance. However, the response of food webs to intensification was different for some contexts. Intensification sharply decreased connectance in Mediterranean and Alpine settlements, and it increased basal tetrapod proportions and compartmentalization in Mediterranean forest and Atlantic croplands. Besides, intensive urbanization especially favoured longer trophic chains and lower omnivory. By favouring mesopredators in most contexts, intensification could undermine basal tetrapods, the cascading effects of which need to be assessed. Our results support the importance of protecting top predators where possible and raise questions about the long‐term stability of food webs in the face of human‐induced pressures.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Cardiac activity in walleye ( Sander vitreus ) during exposure to and recovery from chemical anaesthesia, electroanaesthesia and electrostunning - Connor H. Reid; Graham D. Raby; Matthew D. Faust; Steven J. Cooke; Christopher S. Vandergoot (Journal of Fish Biology, 2022)
Handling and conducting invasive procedures are necessary for aspects of fisheries science, invariably inducing a stress response and imposing energetic demands on fish. Anaesthesia or immobilisation techniques are often used in an attempt to mitigate stress and improve welfare, yet these also come with their own impacts on post‐release recovery. Here, the authors investigated whether changes in cardiac activity (heart rates over time, heart rate maxima, and scopes) differed in adult walleye ( Sander vitreus ) anaesthetised with AQUI‐S® 20E (eugenol), electroanaesthetised with a transcutaneous electrical nerve stimulation (TENS) unit or electrostunned with a commercially developed stunning unit. This experiment was divided into two trials. In the first trial, fish were implanted with heart rate loggers and left to recover for c. 4 days. In the second trial, fish were implanted with heart rate loggers, given 3 days to recover and re‐exposed to their initial treatments (excluding surgery). Post‐treatment cardiac activity was quantified for both trials. Although highly variable across individuals, the authors found no significant differences in heart rate changes over time or recovery times among treatments. Maximum heart rates were consistent among treatment groups, yet significant differences in heart rate scope provided further evidence of strong interindividual variation in the second trial. Based on these results, the authors did not identify any welfare‐relevant differences or concerns associated with one treatment over another. Further investigations of the relationships between measures of cardiac function and other physiological stress markers would be beneficial towards identifying best practices for fish handling in fisheries science.

Environmental and Spatial Influences on Biogeography and Community Structure of Saltmarsh Benthic Diatoms - Craig J. Plante; Kristina Hill-Spanik; Maxwell Cook; Connor Graham (Estuaries and Coasts, 2021)

Ad libitum water consumption off-sets the thermal and cardiovascular strain exacerbated by dehydration during a 3-h simulated heatwave - Connor Graham; Nathan B. Morris; Amy E. Harwood; Ollie Jay (European Journal of Applied Physiology, 2020)

Novel full-length major histocompatibility complex class I allele discovery and haplotype definition in pig-tailed macaques - Matthew R. Semler; Roger W. Wiseman; Julie A. Karl; Michael E. Graham; Samantha M. Gieger; David H. O’Connor (Immunogenetics, 2018)

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques - Trent M. Prall; Michael E. Graham; Julie A. Karl; Roger W. Wiseman; Adam J. Ericsen; Muthuswamy Raveendran; R. Alan Harris; Donna M. Muzny; Richard A. Gibbs; Jeffrey Rogers; David H. O’Connor (Immunogenetics, 2017)

Major histocompatibility complex haplotyping and long-amplicon allele discovery in cynomolgus macaques from Chinese breeding facilities - Julie A. Karl; Michael E. Graham; Roger W. Wiseman; Katelyn E. Heimbruch; Samantha M. Gieger; Gaby G. M. Doxiadis; Ronald E. Bontrop; David H. O’Connor (Immunogenetics, 2017)

Replication and fine mapping of asthma-associated loci in individuals of African ancestry - David B. Kantor; Cameron D. Palmer; Taylor R. Young; Yan Meng; Zofia K. Gajdos; Helen Lyon; Alkes L. Price; Samuela Pollack; Stephanie J. London; Laura R. Loehr; Lewis J. Smith; Rajesh Kumar; et al. (Human Genetics, 2013)

Assessment of Lumiracoxib Bioavailability from Targeted Sites in the Human Intestine Using Remotely Activated Capsules and Gamma Scintigraphy - Ian R. Wilding; Alyson L. Connor; Polly Carpenter; Christiane Rordorf; Janice Branson; Slavica Milosavljev; Graham Scott (Pharmaceutical Research, 2004)